Bimbingan Kelompok Teknik Simulasi Untuk Meningkatkan Kompetensi Public Speaking Bagi Masyarakat Desa Wisata - Dyah Amelia Susanti; Ari Khusumadewi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
Providing information services by tourist village communities for tourists requires good public speaking competencies. Public speaking competence for tourism village communities plays an important role in promoting tourism villages. The tourist village community needs to be able to communicate effectively about the significance of the village's history and cultural wealth to local and foreign tourists. For this reason, the purpose of this study is (1) to describe group guidance simulation technique, (2) to explain Spitzberg and Cupach's theory of public speaking competence, (3) to identify factors of group guidance simulation technique to improve public speaking competence, (4) to analyze the role of group guidance simulation technique to improve public speaking competence. The method used in this research is a literature review. Sources of literature used, namely sourced from Google Scholar, Researchgate, Google Books, and Publish or Perish, are limited to the last 5 years of publication from 2020 to 2024. The results of this study indicate that group guidance using simulation techniques is proven to be able to improve public speaking skills in tourist village communities. With this group guidance simulation technique, the tourist village community gets an interesting experience in understanding public speaking competencies consisting of motivation, knowledge, and skills.